The effect of liquid organic fertilizer from tofu industrial waste and EM4 on the growth of mustard greens (Brasicajuncea L.) - Intannia Eka Putri Sugiharti; Ahmad Raksun; I Gde Mertha (Jurnal Pijar Mipa, 2022)
This study aimed to determine the effect of liquid organic fertilizer (LOF) from tofu industry waste, EM4, and their combination on the growth of mustard greens (Brassica juncea L.) and to determine the most optimal dose to increase the growth of mustard greens. This study used a factorial Completely Randomized Design (CRD) consisting of 2 factors. The first factor is the dose of POC from the tofu industry waste, and the second is the dose of EM4. Each factor has five levels of fertilization with three replications. The treatment of liquid organic fertilizer from tofu industry waste consisted of 0 ml, 25 ml, 50 ml, 75 ml, and 100 ml. The EM4 treatment consisted of 0 ml, 1 ml, 2 ml, 3 ml, and 4 ml/100 ml water. The parameters observed in Green mustard growth were plant height, number of leaves, wet weight, leaf area, and dry weight. The results of the research showed that the POC of tofu waste, EM4, and its combination did not have a significant effect on all parameters.